Desain Pengembangan Kurikulum Pendidikan Agama Islam dan Implementasinya di SD Integral Hidayatullah Kota Bengkulu - Zaleka, Zaleka (UIN Fatmawati Sukarno Bengkulu, 2021)
The design should encourage teachers to consider the various learning experiences of children obtained outside of school and relate them to learning activities at school. The design should provide a continuous learning experience. The curriculum should be designed to help students develop character, personality, experience, and democratic values that inspire culture. The curriculum design must be realistic, feasible, and acceptable. r. It needs to be understood wisely to be able to deliver the success of educational goals. This study uses a descriptive qualitative approach with a library research method. The results of the study show that Islamic religious education in elementary schools is quite unique, if in the previous period children's thinking power was still imaginative and egocentric, then at this time children's thinking power develops towards concrete, rational and objective thinking. The scope of the study of Islamic religious education is the Qur'an, faith, morals, fiqh/worship, and the history of Islamic culture. The educational methods that can be applied refer to the Quranic method, namely the amstal method, the qishah method, the ibrah mauidzah method, the hiwar jadali method, the uswah hasanah method, and the targhib tarhib method. Meanwhile, Islamic religious education can be carried out verbally or non-verbally, in writing or non-writing which is intended to measure intellectual competence, social competence, social competence and spiritual competence. Thus, Islamic religious education is expected to produce humans who always strive to perfect faith, piety, and morals, and actively build Islamic civilization.